DAMPAK FILM SERIAL TERHADAP AKUISISI BAHASA ANAK - Liya Umaroh; Hetty Catur Ellyawati (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2016)
Childrens language skills already possessed since they were born in the world (nature). However, the development of language acquisition such as morphology, syntax, phonology, and pragmatics can be obtained from surrounding environment (nurture). Between heredity and environmental factors are closely related to the process of language acquisition. By now, many sources of childrens language acquisition demand all parents for accompanying their children's activities. One of the example is the accompaniment while they watched serial film. Various kinds of events can be enjoyed by children without considering the feasibility of the program. Therefore, this study focused on serial film entitled "Balveer". The reason for choosing "Balveer" is because the Indian Film still dominated until right now and most of children merely never missed in every episode. Qualitative research method and case study are used in this research. The result shows that in the age of five years old, children can produce language properly, in term of morphology, syntax, phonology, and pragmatics. On the other hand, a serial film also helps children in their language acquisition, many new words, clauses, and sentences automatically imitated and directly produced. Parents take important role to guide their children in their language acquisition.